Cytokine gene expression and pathology in experimental Pasteurella multocida infection in mice - KRISHNAMOORTHY, P; DAS, SANGITA; SHOME, B R; ROY, PARIMAL (The Indian Journal of Animal Sciences, 2017)
The study was conducted to know the pathology and cytokine gene expression studies in experimental infection with Pasteurella multocida in mice. Swiss albino mice (20) were inoculated with P. multocida (200 μl of 1 × 108 cfu/ml) and control mice with sterile PBS intraperitoneally and sacrificed 4 mice at 6, 12, 18 and 24 h. Mice showed dullness, lethargy and unable to move at 18 and 24 h after inoculation. Histopathology revealed changes in liver, kidney, spleen, lung and no observable changes in heart and abdominal muscles. Liver showed septicemia condition and acute bronchopneumonia of lung at 24 h. TNF-α gene showed 20-fold increase in liver and spleen and 5-folds in kidney. There was upregulation of pro-inflammatory cytokines in liver, kidney, spleen and IL–10 gene at later periods of infection which is a new finding, needs further study. Thus, the present study indicated that increase in tissue cytokine gene expression concurred with histopathological changes were attributed to the pathogenesis of Pasteurellosis in mice.